IRAQI CONSTITUTION: ADVANCING THE DIALOGUE OF RELIGIOUS FREEDOM - Matalak, Ghaleb Yassin Farhan (European journal for philosophy of religion, 2023)
The Iraqi constitution of 2005 grants freedom of religious thought, belief and practice for all religions. This study was also based on the premise that the constitutional rights are not adhered to in Iraq, even by government officials, which could be due to the absence of suitable legislations subsequent to the framing of the constitutional provisions. An analytical and descriptive research design was adopted for this study. Data was collected from primary and secondary sources through documentation research and evaluation of historical sources. The primary data comprised Articles of the Iraqi constitution, and a few national and international legal instruments related to religious freedom. Secondary data included empirical research studies, books, articles and other published sources. This study therefore took the form of an empirical legal research as it involved the issues of constitutional reforms in the field of religious freedom. A comparative approach was adopted in analyzing the documents about religion and politics related to both the Arab region and the West. The focus was on the measures that should be adopted to advance the dialogues of religious freedom and maintain religious neutrality in all government policies. The study found out that there were apparent contradictions between the constitutional provisions and the State Laws. Similarly, the Iraqi civil and penal codes remain silent regarding legal remedies for the violation of constitutional provisions.